Training on the preparation of internal audit instruments on the application of Good Manufacturing Practices (GMP) for class B catering services - Amiroh Amiroh; Armita Athennia; Sarah Mardiyah (Community Empowerment, 2022)
Good Manufacturing Practices (GMP) is the most fundamental food safety system, and it is required in the catering business. This community service strives to educate personnel in class B catering services, particularly hospital food providers, how to construct internal audit instruments for the application of GMP catering services. The online session was attended by 59 people from 23 different institutions. Following the training, 66.1% said that conducting an internal audit of GMP implementation was simple. A total of 98.3% said they are prepared to conduct routine internal audits on a regular basis, albeit in stages. Aside from that, all participants reported satisfaction with the training's implementation, with 82.76 percent stating that they were extremely satisfied.